Validation of the updated ArthroS Simulator: face and construct validity of a passive haptic virtual reality simulator with novel performance metrics - Garfjeld Roberts, P; Guyver, P; Baldwin, M; Akhtar, K; Alvand, A; Price, A; Rees, J (Springer Verlag, 2016)
Purpose: To assess the construct and face validity of ArthroS, a passive haptic VR simulator. A secondary aim was to evaluate the novel performance metrics produced by this simulator. Methods: Two groups of 30 participants, each divided into Novice, Intermediate or Expert based on arthroscopic experience, completed three separate tasks on either the knee or shoulder module of the simulator. Performance was recorded using 12 automatically-generated performance metrics, and video footage of the arthroscopic procedures. The videos were blindly assessed using a validated global rating scale (GRS). Participants completed a survey about the simulator’s realism and training utility. Results: This new simulator demonstrated construct validity of its tasks when evaluated against a GRS (p≤0.003 in all cases). Regards it’s automatically-generated performance metrics, established outputs such as time taken (p≤0.001) and instrument path length (p≤0.007) also demonstrated good construct validity. However, two-thirds of the proposed ‘novel metrics’ the simulator reports couldn’t distinguish participants based on arthroscopic experience. Face validity assessment rated the simulator as a realistic and useful tool for trainees, but the passive haptic feedback (a key feature of this simulator) is rated as less realistic. Conclusion: The ArthroS simulator has good task construct validity based on established objective outputs, but some of the novel performance metrics couldn’t distinguish between surgical experience. The passive haptic feedback of the simulator also needs improvement. If simulators could offer automated and validated performance feedback, this would facilitate improvements in the delivery of training by allowing trainees to practice and self-assess.